PENGARUH LOCUS OF CONTROL, PENGALAMAN, SKEPTISME PROFESIONAL, DAN TIME BUDGET PRESSURE TERHADAP KUALITAS AUDIT PADA KANTOR AKUNTAN PUBLIK DI BALI - Putu Yulia Suwantari; I Ketut Yudana Adi (Journal Research of Accounting, 2020)
This study aims to determine the effect of locus of control, experience, professional skepticism, and time budget pressure on audit quality of the Public Accounting Firm in Bali. The population on this study is the auditor who works at the Public Accounting Firm in Bali that registered in the Directory Indonesian Institute of Certified Public Accountants (IICPA) in 2019 with population is 107 auditors. Sampling technique use non probability sampling technique that is purposive sampling. The sample in this study is 67 auditors. Data collection technique use interview and questionnaire. Data analysis technique use statistics using the SPSS (Statistical Package for Social Sciences) application program. Tests conducted include: instruments test, classic assumption test, multiple linear regression analysis, statistical test t, statistical test F, and coefficient of determination test (R2 ). The result shows that partially locus of control, experience, professional skepticism, and time budget pressure have positive and significant effect on audit quality of the Public Accounting Firm in Bali. Locus of control, experience, professional skepticism, and time budget pressure simultaneously affect audit quality of the Public Accounting Firm in Bali.